BE_ZIVILSTRAF BK 2021 63 vom 27. Januar 2021 - BE Obergericht (2021)
Nichtanhandnahme \"Zivilrechtliche Anzeige\" vom 12. Dezember 2020 wegen Verstössen gegen die BV, die EMRK und die ZPO | Einstellung/Nichtanhandnahme